2013
DOI: 10.1016/j.jadohealth.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sedentary Behaviors: Correlates Differ for Television Viewing and Computer Use

Abstract: Purpose Sedentary behavior is associated with obesity in youth. Understanding correlates of specific sedentary behaviors can inform the development of interventions to reduce sedentary time. The current research examines correlates of leisure computer use and television viewing among California adolescents. Methods Using data from the 2005 California Health Interview Survey (CHIS), we examined individual, family and environmental correlates of two sedentary behaviors among 4,029 adolescents: leisure computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 34 publications
10
73
1
10
Order By: Relevance
“…The use of VG and PC was higher among boys in studies conducted in the United States 11 and South Korea 12 . The use of TV was higher among girls in South Korea 12 and Brazil 13 .…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The use of VG and PC was higher among boys in studies conducted in the United States 11 and South Korea 12 . The use of TV was higher among girls in South Korea 12 and Brazil 13 .…”
Section: Discussionmentioning
confidence: 81%
“…Different studies around the world have shown that exposure to screen time is significantly different between boys and girls [7][8][9][11][12][13] . The use of VG and PC was higher among boys in studies conducted in the United States 11 and South Korea 12 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations